How to tell the time - Sean McArdle (UK DK publications, 2023)
To tell the time, you need to understand how to read both the hour and minute hands on a clock face. The hour hand (the shorter, thicker one) points to the hour, while the minute hand (the longer, thinner one) indicates the minute